Pengaruh Kemiskinan terhadap Angka Kematian Ibu dan Harapan Hidup Wanita Tahun 2024 di Jambi - Astuti, Syurmi (Universitas Batanghari Jambi, 2024)
This study aims to explore the influence of poverty on maternal mortality and female life expectancy in Jambi Province in 2024. Using a quantitative approach with a descriptive and analytical research design, this study analyzed secondary data from the Central Statistics Agency (BPS) and the Health Office, as well as primary data through surveys and interviews. The results showed that high poverty levels significantly affect maternal and women's health. The maternal mortality rate in Jambi Province reached 200 per 100,000 live births, with higher rates found among poor families compared to better-off families. Life expectancy for women in poor areas is also lower, at around 68 years, compared to 74 years in better-off economic groups. These findings underscore the need for more effective policies to improve access to health services and quality of life among poor families.